2016
DOI: 10.1002/mame.201600377
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Silicone Rubber Foam with Tailored Porous Structures by Supercritical CO2

Abstract: In spite of great concern on the wide application of silicone rubber foams, few works have been reported about easy‐operating foaming method. In this study, the effects of silica content and foaming process on the porous structure of high‐temperature‐vulcanized silicon rubber foams are evaluated, which are prepared by supercritical CO2 at different conditions, with fumed silica used for reinforcement. Silicone rubber foams with cell size in 8–120 μm, cell density in 105–108 cm−3, and density between 0.45 and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…On the other hand, the cell size and cell density are mainly determined by the diffusivity and solubility of PFA. Yan and coworkers reported that when the saturation pressure increases (fixed temperature), the cell size decreases resulting in narrower cell size distributions [ 51 ]. Hence, increasing the CO 2 saturation pressure in their case led to more molecules being absorbed by the silicone rubber matrix leading to a more important homogeneous nucleation effect producing a higher number of larger cells.…”
Section: Structural Featuresmentioning
confidence: 99%
“…On the other hand, the cell size and cell density are mainly determined by the diffusivity and solubility of PFA. Yan and coworkers reported that when the saturation pressure increases (fixed temperature), the cell size decreases resulting in narrower cell size distributions [ 51 ]. Hence, increasing the CO 2 saturation pressure in their case led to more molecules being absorbed by the silicone rubber matrix leading to a more important homogeneous nucleation effect producing a higher number of larger cells.…”
Section: Structural Featuresmentioning
confidence: 99%
“…Moreover, lightweight porous CPCs characterized by low density, high specific mechanical properties, and high capability to adsorb impact-energy have great potential in several application sectors [ 27 , 28 ]. The electrical conductivity of CPCs in which the conductive fillers were randomly dispersed improved significantly after a foaming procedure because of the redistribution of conductive fillers and their constraint in a reduced volume (struts and walls of the porous material) with consequent reduction of a distance between adjacent conductive fillers [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…silica. Yan et al 139 also used high amount of silica up to 60 phr but without precrosslinking. They achieved foam with cell size in the range between 8 and 120 mm, cell density between 10 5 and 10 8 cells/cm 3 and density between 0.45 and 0.9.…”
Section: Co 2 Foamingmentioning
confidence: 99%